True Stress-Strain Behavior of Al-based Cast Automotive Alloy Under Different Ageing Conditions and the Effect of Trace Zr - Shoummo, Mashiur Rahman; Khan, Akib Abdullah; Kaiser, Mohammad Salim (Universitas Negeri Malang, 2022)
A thorough investigation has been carried out on the Al-12Si-1Mg-1Cu-1Ni automotive alloy considering different properties, specially mechanical properties associated with true stress and true strain with Zr addition of trace amount. A commercially available piston is melted to produce the alloy, and trace amount of Zr is added to make another. The base alloy along with the Zr added alloy had been applied to homogenization, solution treatment, quenching, and ageing in order to get the age-hardening response. The alloys have been heat-treated at 25 ºC, 200 ºC, and 300 ºC, respectively, for four hours for attaining the under, peak and over-aged states, respectively. During ageing, Al2Cu and Mg2Si phases are formed in the aluminium matrix leading to peak-aged strength, which is reduced at over-aged state because of coarsening of precipitation and recrystallizing, shown by the tensile and hardness properties. When Zr is added to the alloy, Al3Zr phases appear while casting and heat-treatment, resisting the drop of strength at over-aged state. It is visible in the stress-strain diagram that at over-aged conditions, the alloy with trace Zr shows improved strength and ductility. In the micrographs of Zr added alloy, finer distributed grains are visible through the grain refinement of Zr, which also prevents recrystallization at over-aged conditions. The homogeneity of the grains as a result of the Zr addition's microstructural change was further confirmed by fractography. It is clear that adding Zr to such alloys does not greatly increase their strength, but it does restrict the declining of strength by preventing the production of thermally stable Al3Zr precipitates, which coarsens the resisting behavior of various intermetallics in the thermally damaged alloy.